Examining the Motivations and Barriers Influencing the Decisions of Louisiana State University College of Agriculture Freshmen to Participate in International Experiences - Shelli Danjean; J C Bunch; Joey Blackburn (Journal of International Agricultural and Extension Education, 2015)
Over the past decade, universities in the United States (U.S) have increased time and financial investments put toward internationalizing their curricula, particularly in efforts to increase students’ participation in international experiences (IEs). Despite efforts, only 10% of U.S students participated in an IE in the 2011/2012 academic year, of which only 1.3% included students in agriculturally-related majors. The purpose of the study was to examine the motivations and barriers influencing the decisions of College of Agriculture (CoA) freshmen to participate in an international experience (IE). The majority of freshmen were interested in an IE, and they perceived their participation would be at least somewhat important to their education and future career. Overall life experience gained and looks good on a résumé were perceived as the most important motivations. Cost and lack of information were the greatest barriers perceived by freshman students. Freshmen who perceived the most motivations also had greater interest in an IE and viewed an IE as very important, while freshmen who perceived the fewest motivations were those who did not perceive an IE as important. It can be recommended that students who have participated previously in an IE deliver presentations during first year experience courses. These presentations should highlight global components of the curriculum using practical, job-oriented instructional methods that focus on the overall life experiences, career benefits, and résumé strength. To eliminate cost barriers and increase student participation in IEs, CoA administrators and faculty members should work with freshmen to help them locate scholarship opportunities early on in their college career.
Keywords: motivations; barriers; international experiences; undergraduate education